Identifying the Best Herbicides for Weed Control in Chicory (Cichorium intybus) - Angelika Astaykina; Sergey Elansky; Evgeniy Kubarev; Daniil Semeniushkin; Irina Smirnova; Elena Chudinova; Vladimir Demin; Alexander Nikolaev; Sergey Shoba (Agriculture, 2023)
Chicory (Cichorium intybus) is a commercially cultivated root crop in many countries of the world. Weeds have a depressing effect on the growth and development of root chicory. There are currently no herbicides registered for use on chicory in the Russian Federation. The objective of this work was to identify potential herbicides for controlling a broad range of weed species under the soil and climatic conditions of the Russian Federation. For the field experiment, herbicides were selected according to: (1) previous studies in USA, EU and South Africa; (2) the spectrum of weeds controlled; and (3) the probability of crop damage. All the herbicides used were registered in Russia for the control of certain weeds in other crops. Crop biomass, damage, and weed control were assessed to identify suitable herbicides. The results suggested that the best weed control herbicides would be a Zeta, SC (100 g/L imazethapyr) and Paradox, SC (120 g/L imazamox). These herbicides controlled, on average, 80% or more of the dicotyledonous weeds such as lamb’s quarters (Chenopodium album), field pennycress (Thlaspi arvense), and sow thistles (Sonchus spp.). Since these herbicides do not reduce chicory biomass, they can be considered for registration or use on chicory.